The complex lives of community college students pursuing career technical degrees and certificates: an exploration of time prioritization from students’ perspectives - Garcia-Galicia, Ramiro (Kansas State University, 2024)
Community colleges prepare nontraditional students for a variety of careers. Although the colleges promote flexible class schedules and faculty who understand their students’ social and economic statuses, nontraditional students often need help prioritizing their college responsibilities. The purpose of this phenomenological qualitative study was to examine adult nontraditional career and technical education (CTE) students’ motivations, personal needs, and inside- and outside-classroom influences on the ways they prioritized their time. The study addressed three primary research questions: What are the overall responsibilities of nontraditional CTE students seeking careers? How do nontraditional CTE students prioritize college and personal demands? Where and from whom are nontraditional CTE students receiving guidance related to prioritizing their time to reach their educational goals? In this qualitative study, participants’ lived experiences could be categorically grouped into two categories: participants with dependents and participants without dependents. Using reciprocating determinism and hierarchy of needs theories, this study found nontraditional CTE students with dependents prioritized their college responsibilities last. They had to make lose–lose decisions that negatively impacted their education, family obligations, or education if they could not find empathetic employers or faculty to help them navigate their responsibilities. Based on the findings of this study, different teaching strategies are recommended among subgroups of CTE nontraditional students. This suggests that colleges consider changing how committees evaluate future professors to meet the needs of nontraditional community college students.
Keywords: Nontraditional students; Career and technical education; Stackable certificates; Student retention; Student success; Prioritization; Reciprocating determinismTrades or trade careers